Optimisation of culture condition for Sacha Inchi (Plukenetia volubilis) Callus induction - Rosle, Norsyahira; Mohd Jalil, Jasrina; Abdul Wahab, Widya; Yunus, Muhamad Fahmi; Meenakshi Sundram, Tamil Chelvan (2021)
Plukenetia volubilis or commonly known as sacha inchi produces wide range of health‐promoting bioactive compounds. The plant has large edible seeds that are rich in phenolics, minerals and essential fatty acid, such as omega 3, omega 6, omega 7 and omega 9. In vitro cultures could serve as alternative in producing many essential sacha inchi bioactive compounds. In this study, as an initial step towards initiating in vitro cultures, the effect of 2,4-D and TDZ on callus induction using leaves and male flower as explants were investigated. Surface sterilization of the sacha inchi explants were done by using 70% ethanol (30 seconds) and 0.5% sodium chloride (8 minutes) to overcome culture contamination. The sterilization method resulted in 82.5% and 95% survival rate for leaf and flower explants, respectively. Next, for callus induction the explants were cultured on MS medium supplemented with different concentrations of 2,4-D and TDZ, either alone or in combination and grown in 24 hours dark photoperiods. The morphology and size of callus obtained varied according to the treatment. Callus produced are either friable or compact with either creamy white, pure white or brownish colour. For both explants, the best response in term of callus size, friability and creamy white callus was obtained when cultured on MS medium supplemented with 3% (w/v) sucrose in combination with 1.0 mg/L 2,4-D and 0.005 mg/L TDZ.